The Effectiveness of Picture Storybook Integrated with Interactive Worksheets in Enhancing Primary Students’ Global Diversity - Evan Pranawa; Anwar Senen; Albi Anggito (FKIP - Universitas Riau, 2026)
Learning that instills the values of tolerance, empathy, and respect for differences from an early age is very important in shaping students' global diversity attitudes. However, the learning process in elementary schools often still focuses on cognitive aspects and does not provide many socially and emotionally meaningful learning experiences. This study aims to determine the effectiveness of using picture storybooks integrated with interactive student worksheets in improving the global diversity attitudes of elementary school students. This study used a quasi-experimental method with a pretest-posttest control group design. The experimental group received treatment using picture storybooks integrated with interactive student worksheets, while the control group used PowerPoint media and conventional student worksheets. The results of the analysis showed that the average N-Gain value in the experimental class was 0.73 in the high category, while in the control class it was 0.47 in the medium category. The independent t-test showed a Sig. (2-tailed) value = 0.000 < 0.05, which means there was a significant difference between the two groups. Thus, the use of picture story books integrated with interactive student worksheets has proven effective in improving students' global diversity attitudes through more reflective, empathetic, and contextual learning experiences.